(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper focuses the Critical views on ‘Gender Perspectives in Kavita Kane’s fiction ’Sita’s Sister’. Kavita Kane, an Indian journalist became progressive writer, spotlighted feministic view through the retold Indian mythologies which strengthen ladies’ subjugation in any respect levels of society. the existing studies makes a speciality of how the machine disregarded women when it came to taking a selection consisting of her marriage. In this paper, Kavita Kane’s perspectives on gender roles are offered from the factor view of Urmila, an individual inside the Indian epic The Ramayana. The protagonist within the novel Sita’s Sister, Urmila, helps her husband’s acts without wondering to run the show inside the circle of relatives as well as in ruling the dominion however raises her voice whilst all the students cross on discussing the responsibilities and rights of the guys in step with the Dharma. She questions how Dharma can forget about the opposite gender which are half under the sky. The look at is conducted the usage of gender theory because it opens strange views for the way to understand people of their numerous contexts such as gendered structures and norms.